KEMAMPUAN MENYIMAK BERITA SISWA KELAS VIII SMP YLPI MARPOYAN PROGRAM PLUS PEKANBARU - Frederica, Nadya (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACT: This study discusses the ability to listen to news eighth grade students of SMP YLPI Marpoyan program plus Pekanbaru. This study aims to determine the listening skills of eighth grade students of SMP news YLPI Marpoyan program plus Pekanbaru. The sample used in this study in which the total sample, total sample of 48 people. The method used is the method description. The subjects were eighth grade students of SMP YLPI Marpoyan program plus Pekanbaru. The data collection techniques used were engineering tests. This research data analysis techniques to analyze data about essay writing skills description, by collecting student worksheets that have been done while listening to the news to be analyzed. From the research results obtained by the ability to listen to the news in determining what elements (what) eighth grade students of SMP YLPI Marpoyan Pekanbaru programs plus high category with an average of 91.7 (91.7%) of the total score of 100 an student. The ability to listen to the news in determining element who (whom) eighth grade students of SMP YLPI Marpoyan program plus Pekanbaru high category with an average of 92.7 (68.357%) of the total score of 100 an student. The ability to listen to the news in determining element when (when) the eighth grade students of SMP YLPI Marpoyan program plus Pekanbaru category with the average being 72.9 (72.9%) of the total score of 100 an student. The ability to listen to the news in determining where elements (where) Junior High School eighth grade students SMP YLPI Marpoyan plus programs Pekanbaru high category with an average of 95.83 (95.83%) of the total score of 100 an student. The ability to listen to the news in determining elemental why (why) eighth grade students of SMP YLPI Marpoyan Pekanbaru program plus high category with an average of 86.5 (86.5%) of the total score of 100 an student. The ability to listen to the news in determining how elements (how) Junior High School eighth grade students SMP YLPI Marpoyan programs plus Pekanbaru Medium category with an average of 70.83 (70.83%) of the total score of 100 per student. It can be concluded the average ability of listening to news of the eighth grade students of SMP YLPI Marpoyan Pekanbaru overall program plus high category with a mean overall 86.44. (86.44%) of the total score of 100 an student. Keywords: Listen, News